1998
DOI: 10.1002/(sici)1097-0274(199809)34:3<288::aid-ajim12>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome following maternal organic solvent exposure: A meta-analysis of epidemiologic studies

Abstract: Background Evidence of fetal damage or demise from occupational organic solvent levels that are not toxic to the pregnant woman is inconsistent in the medical literature. The risk for major malformations and spontaneous abortion from maternal inhalation of organic solvent exposure during pregnancy was summarized using meta‐analysis. Methods Medline, Toxline, and Dissertation Abstracts databases were searched to locate all research papers published in any language from 1966 to 1994. Included were studies that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 26 publications
1
56
0
1
Order By: Relevance
“…In 2000, anencephaly had a reported rate of 9.40 per 100,000 live births in the United States, [Mathews, 2002]. Of interest, McMartin et al [1998] produced similar findings (i.e., the same malformations with approximately the same odds ratios) in women exposed to organic solvents.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In 2000, anencephaly had a reported rate of 9.40 per 100,000 live births in the United States, [Mathews, 2002]. Of interest, McMartin et al [1998] produced similar findings (i.e., the same malformations with approximately the same odds ratios) in women exposed to organic solvents.…”
Section: Discussionmentioning
confidence: 95%
“…These compounds have been shown to increase the risk of MMs significantly (ORs ¼ 1.64, CI 95% : 1. 16-2.30, N ¼ 7,036) [McMartin et al, 1998]. …”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study where the risk of congenital malformations in relation to occupational painting has been investigated by a register-based approach. Some previous studies have focused on maternal exposure to volatile organic compounds (VOC) and have shown an increased risk of congenital anomalies among the children (19)(20)(21).…”
Section: Discussionmentioning
confidence: 97%
“…For example, maternal exposure to organic solvents has been associated with spontaneous abortion in several studies (Pastides et al, 1988;Taskinen et al, 1989;Lindbohm et al, 1990;Lipscomb et al, 1991;Windham et al, 1991;Schenker et al, 1995). However, a meta-analysis of five of these studies resulted in a non-significant odds ratio (McMartin et al, 1998). Two recently published prospective pregnancy studies reported an increased risk of pregnancy loss associated with serum levels of dichlorodiphenyltrichloroethane (DDT) and its metabolite, dichlorodiphenyldichloroethene (DDE).…”
Section: Mortalitymentioning
confidence: 99%